TEACHER’S WRITTEN CORRECTIVE FEEDBACK ON LANGUAGE FEATURES ON STUDENTS’ WRITING - Nensy Triristina (Widya Mandala Surabaya Catholic University, 2018)
The objective of this study was to investigate the type of corrective feedback used by a teacher on students’ writing. The subjects of the study were twelve students of tenth graders of a private senior high school in Ponorogo selected based on pre-determined set criteria. The study used a qualitative method and the sources of data collected in this study were the teacher’s written corrective feedback on language features which focused on three categories of errors: subject-verb agreement, word choice, and sentence structure in the students’ descriptive texts. The data gathered were processed by analyzing and interpreting the teacher’s written corrective feedback using Ellis’s typologies of corrective feedback (2009) namely: direct, indirect, and metalinguistic corrective feedback. The result of the study shows that the type of corrective used by the MAN 2 Ponorogo teacher to correct the students’ descriptive writing was typology corrective feedback proposed by Ellis (2009). The corrective feedbacks used by the teacher were as many as 108 occurrences in total. The occurrences of direct corrective feedbacks were 37 (40,65%) on subject verb agreement errors, 20 (21,98%) word choices, and 34 (37,37%) sentence structures, while the indirect corrective feedback were 3 (21,42%) subject verb errors, 4 (28,58%) word choices, and 7 (50%) sentence structures, and metalinguistic on subject verb errors, word choices, and sentence structures used by the teacher was only 1 (3,33%) of each. It was later concluded that the type of corrective feedback mostly used by the teacher in revising their students’ grammatical errors was direct corrective feedback.